Рыбы озера Выгоновского и их промысел. Сообщение II - Воронин, Ф.Н.; Крылов, В.В. (Вестник зоологии, 1971)
The characteristic is given of morphological characters, growth rate and catch oi predatory and some other species of fish in lake Vygonovskoe. As to the data of fishery statistics for 1955—1967 the following species are of the greatest importance: Carassius aura/us gibelio (В 1 о с h) — 55.5%; Esox lucius — (19.1 %); Rutilus rutilus (L.) — 5.45%: C. carassius (L.) — 13%; Abramis brama (L.) — 0.64%;Perca fluviatilis (L.) — (0.39%). As a result of repairs in the Oginsky canal and the lock the water level in the lake became 0.5—0.6 m higher. This created an additional spawning and fattening area, which makes it possible to increase with acclimatization of Carassius auratus gibelio the fish productivity in the lake from 13.5 kg/ha in 1948—1954 to 62.8 kg/ha in 1955—1967 at an average. C. auratus gibelio and Esox lucius as well as Abramis brama, when regulating the water level should be considered as promissing fishery species for the lake.